Global Analysis of the Hydrologic Sensitivity to Climate Variability - Dominguez, Marisol (ScholarWorks@UTEP, 2021)
Identifying the regions with greatest changes in their hydrologic behavior under extreme weather events in the 21st century, constitutes a study priority of global impact. Here, we present a global assessment assessing the sensitivity of the world’s water landscapes to climate variability during 2001-2016, using a new metric called the Hydrologic Sensitivity Index (HSi). This equation is based on the well-known Budyko curve that uses annual values of Potential and Actual Evapotranspiration (PET and AET), and Precipitation (P), to assess the hydrologic behavior of a location under a given climatic condition by plotting the Evaporative Index (AET/P) against the Dryness Index (PET/P). For values i ≥1: Sensitive and i<1: Resilient. Also, since elevation, slope and aspect are the three of the defining factors in temperature and humidity regimes, we evaluate their influence on HSi. Overall, majority of the world’s biomes display tendency toward drier state. Particularly, we identify the regions with hydrologic sensitivity to climate variability in tropical rainforests accompanied with decreasing water yields and warmer/drier conditions evident along southernmost part of Amazon and central part of the Congo basin. High sensitivity is also seen along easternmost Canadian and Eurasian arctic tundra and boreal forests with increasing water yield trends and dominant warmer/drier climate conditions. The hydrologic sensitivity is amplified at high elevations and steep-sloped terrain outlining the importance of the topography in modulating these effects. We direct the attention towards climate warming resulting in decreased forest cover as potential mechanism driving the decreasing water yield patterns in tropical zones, while snow melt and increasing precipitation in the tundra and boreal forests resulting in surplus water yields. Our global study highlights the particular locations with greatest hydrologic changes to climate variability while outlining the main water yield and climate directions—a study that ...